PENGARUH KURS SPOT DAN KURS FORWARD DALAM MEMPREDIKSI FUTURE SPOT PADA PASAR VALAS KAWASAN ASIA TENGGARA - I Gusti Ayu Kade Diana Yanthi; Luh Gede Sri Artini (Faculty of Economics and Business Udayana University, 2013)
The importance of the activity in foreign exchange occur as the result of the development of international trading and increased international money and capital movement. The vast development of international economic caused economic relationship among countries will be linked to each other and subsequently improve trading activities in their goods, money and capital flows. The variables used in this study are spot, forward and future spot. Based on the result of Regression Estimation applied in hypothesis on foreign currencies exchange which done simultaneously are proven able to predict future spot. The investor and international economic actor could use spot exchange rate and forward exchange rate as a short terms predictor for the next trimester in 2011.